2013
DOI: 10.1557/mrc.2013.44
|View full text |Cite|
|
Sign up to set email alerts
|

Nanoimprint lithographic surface patterning of sol–gel fabricated nickel ferrite (NiFe2O4)

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…50 This approach has been used to directly fabricate threedimensional structures of multicomponent oxides like indium tin oxide and nickel ferrite. 51,52 Photosensitive ethylhexanoatebased oxide patterning has been reported that utilizes photobreakable precursors rather than photo-curable monomers. 34 Recently, polymerizable sol-gel approach (PSG) has emerged as a promising method for rapid direct nanoimprinting of a host of metal oxides such as TiO 2 , ZrO 2 , Hf 2 O 5 amongst others.…”
Section: Introductionmentioning
confidence: 99%
“…50 This approach has been used to directly fabricate threedimensional structures of multicomponent oxides like indium tin oxide and nickel ferrite. 51,52 Photosensitive ethylhexanoatebased oxide patterning has been reported that utilizes photobreakable precursors rather than photo-curable monomers. 34 Recently, polymerizable sol-gel approach (PSG) has emerged as a promising method for rapid direct nanoimprinting of a host of metal oxides such as TiO 2 , ZrO 2 , Hf 2 O 5 amongst others.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to previous reports , a sol–gel solution of 0.2 M NFO was prepared by separately mixing 2.4884 g of nickel(II) acetate tetrahydrate (C 4 H 6 NiO 4 · 4H 2 O) and 8.08 g of iron(III) nitrate nonahydrate (Fe(NO 3 ) 3 · 9H 2 O) in 20 mL of 2‐methoxyethanol (CH 3 OCH 2 CH 2 OH) solvent each (all from Sigma–Aldrich). The solutions were stirred at 70 °C in ambient conditions for 2 h before being mixed together for 15 min and allowed to cool to room temperature.…”
Section: Sample Synthesis and Experimental Detailsmentioning
confidence: 99%
“…At present, this is accomplished through doping and alloying , but a constraint on device manufacturing remains due to the limitations on material selection . Recently, however, we reported a method to reduce the coercivity in single and multilayered thin films using surface patterning. By affecting only coercivity and maintaining the saturation magnetization, texture and hysteresis curve shape, we eliminate many material selection constraints; one can design devices starting with the most suitable material and pattern the surface to minimize coercivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…
In Rasic et al 1 , the miller indices are displayed incorrectly in two instances: On page 209, first column, fifth line, (111) direction should be <111> direction. On page 209, second column, seventh line, <111> family should be {111} family.
…”
mentioning
confidence: 99%